Cardiac-derived stem cell-based therapy for heart failure: progress and clinical applications. (March 2013) - Tang, Yaoliang L; Wang, Yingjie J; Chen, Lijuan J; Pan, Yaohua H; Zhang, Lan; Weintraub, Neal L
Stem cell-based therapy is emerging as a promising strategy to treat end-stage heart failure, a leading cause of morbidity and mortality. Stem cells can be isolated from a variety of sources and exhibit unique characteristics that impact their potential therapeutic utility. The adult heart contains small populations of committed, multipotent cardiac stem cells (CSC), which are adapted to the cardiac microenvironment and participate in postnatal physiological and pathological cardiac renewal or repair. These cells can be isolated, expanded in culture, and administered therapeutically to improve cardiac function in the setting of heart failure. CSC can be differentiated into three distinct cardiovascular lineages and exhibit enhanced paracrine factor production and engraftment as compared with other types of mesenchymal stem cells, which in turn may translate into improved therapeutic efficacy. The cell surface marker expression and phenotype of these CSC, however, depends on the method of isolation, selection and propagation, which likely explains the variable experimental results obtained to date. Moreover, invasive procedures are required to obtain CSC from humans. Early trials using autologous CSC in patients with ischemic cardiomyopathy have demonstrated feasibility and safety, along with variable degrees of therapeutic efficacy in terms of enhancing myocardial viability and cardiac function. Further studies are needed to optimize methods of CSC isolation, manipulation and delivery. If fully realized, the potential of CSC therapy could fundamentally change the approach to the treatment of end-stage heart failure.